Potential Theraputic Effect of Liraglutide in Male Rats Parkinsonn'Disease Model - Ahmed Hazem Abdulkareem; Khulood Majed Alsaraafb; Mustafa Ghazi Alabbassi; Mustafa Mohammed Al- Obaidy (College of Pharmacy / Mustansiriyah University, 2018)
Parkinson's disease (PD) is a progressive neurodegenerative, chronic disease presented by both nonmotor and motor features. The neuronal loss which rich by dopamine in striatum was the main cause for the PD motor symptoms. While neuronal loss in non-dopaminergic areas support PD nonmotor. liraglutide (Glucagon like peptide-1 mimetic), have effect on CNS by decreasing the number of neutrophils infiltration within CNS which reflect anti-inflammatory characteristics in model of intracerebral haemorrhage in mice. This study represent an attempt o investigate the potential therapeutic effect of liraglutide in male rats Parkinson's disease model. Thirty six adult male rats were divided into three equal groups. Rats in group A were treated with saline intraperitoneally for 30 days. Meanwhile these rats in group B and group C were treated with 6- hydroxydopamine (6-OHDA) toxicant unilaterally intrathecal injection in a dose of 8 μg/per rat in 2 μl distal water, to introduce Parkinson model in rats. Group B were treated similar to that of group A with saline intraperitoneally for 30 days, while group C were treated with liraglutide intraperitoneally for 30 days in a dose 25nmol/kg. Histological changes were observed by light microscopy. The histopathological study showed that neurotoxins, that is, 6-OHDA, caused marked hypertrophic changes, infiltration of neutrophils, alterations of architecture, and even cell death in group B. Furthermore, many neurons were shrunken, and darkly stained with small nuclei compared with normal vehicle treated rats of group A. There is marked reversal of neuronal damage or neuronal alterations observed with liraglutide (25 nmol/ kg) treated rats in group C.